A Simple and Modified One Pot Conversion of Carboxylic Acid to Ketone - Sahoo, Debasis; Jana, Samaresh; Sahoo, Sharmistha (Current Organocatalysis, 2023)
Background: Ketone is one of the important functional groups in synthetic chemistry. For this reason, organic chemists focused on the synthesis of ketone starting from various functionalities since nineties. One of the method deals with the conversion of carboxylic acids to ketones in a one pot manner. We have recently reported a one pot transformation of carboxylic acid to ketone using TsCl or MsCl as an activator of carboxylc acid. In our previous reports, two equivalents of organometallic reagent have been used which may not be useful in medicinal chemistry. In this report, we have developed an alternative process for the transformation where only one equivalent of organometallic reagent has been employed. Objective: In present scenario, we are interested to develop a process for the transformation of carboxylic acid to ketone using one equivalent of an organometallic reagent. Methods: A carboxylic acid reacted with tosyl chloride in the presence of a sodium hydride to form a mixed anhydride. Here, the acidic proton was removed from the reaction mixture as hydrogen gas. This mixed anhydride was then treated with one equivalent of an organomagnesium reagent at -30°C to obtain the desired ketone. Results: Following the optimum conditions, a few commercially available carboxylic acids were treated with TsCl, followed by the treatment of phenyl magnesium and methyl magnesium bromide to obtain phenyl and methyl ketones, respectively, in good to excellent yields. Conclusion: A simple and modified one pot method for the conversion of carboxylic acids to ketone has been reported. In this developed process, one equivalent of the organomagnesium reagent has been used to obtain the desired ketone under the optimized reaction conditions.
Keywords: Carboxylic acid